PENGARUH PERBAIKAN SISTEM SECARA BERKESINAMBUNGAN, PENDIDIKAN DAN PELATIHAN, KETERLIBATAN DAN PEMBERDAYAAN KARYAWAN PADA PT. PERKEBUNAN NUSANTARA V SEI PAGAR - Sari Ravita; Restu Restu; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of continuous improvement on employees productivity, education and training on employees productivity, employee engagement and empowerment on employees productivity at PT. Perkebunan Nusantara V Sei Pagar. The methode of data collection was carried out by distributing questionnaires to employees to prove the result of the reserach. The sampling technique used is census methode with totaling 138 respondents. In this study, the data analysis technique used is multiple linear regression analysis with SPSS (Statistical Program For Social Science). The result of this study show that : 1) Continuous Improvement have positive and significant effect on employee productivity, 2) Education And Training have positive and significant effect on employee productivity, 3) Employee Engangement and Empowerment have positive and significant effect on employee productivity.Keywords : Continuous Improvement, Education and Training, Employee Engangement and Empowerment, Employee Productivity